Cutaneous leishmaniasis in northeastern Brazil: a critical appraisal of studies conducted in State of Pernambuco Leishmaniose cutânea no nordeste do Brasil: uma avaliação crítica dos estudos realizados no Estado de Pernambuco - Maria Edileuza Felinto de Brito; Maria Sandra Andrade; Filipe Dantas-Torres; Eduardo Henrique Gomes Rodrigues; Milena de Paiva Cavalcanti; Alzira Maria Paiva de Almeida; Sinval Pinto Brandão-Filho (Sociedade Brasileira de Medicina Tropical (SBMT), 2012)
American cutaneous leishmaniasis (ACL) is a complex disease with clinical and epidemiological features that may vary from region to region. In fact, at least seven different Leishmania species, including Leishmania (Viannia) braziliensis, Leishmania (Viannia) guyanensis, Leishmania (Viannia) lainsoni, Leishmania (Viannia) naiffi, Leishmania (Viannia) shawi, Leishmania (Viannia) lindenbergi, and Leishmania (Leishmania) amazonensis, have been implicated in the etiology of ACL in Brazil, and numerous phlebotomine sandfly species of the genus Lutzomyia have been regarded as putative or proven vectors. Because ACL is a focal disease, understanding the disease dynamics at the local level is essential for the implementation of more effective control measures. The present paper is a narrative review about the ACL epidemiology in Pernambuco, northeastern Brazil. Furthermore, the need for more effective diagnosis, treatment, control and prevention strategies for the affected populations is highlighted. This paper will provide researchers with a critical appraisal of ACL in Pernambuco. Hopefully, it will also be helpful for public health authorities to improve current control strategies against ACL at the state and country levels. A leishmaniose cutânea americana (LCA) é uma doença complexa com características clínicas e epidemiológicas que podem variar de região para região. De fato, pelo menos, sete diferentes espécies de Leishmania, incluindo Leishmania (Viannia) braziliensis, Leishmania (Viannia) guyanensis, Leishmania (Viannia) lainsoni, Leishmania (Viannia) naiffi, Leishmania (Viannia) shawi, Leishmania (Viannia) lindenbergi e Leishmania (Leishmania) amazonensis, têm sido incriminadas na etiologia da LCA no Brasil, e numerosas espécies de flebotomíneos do gênero Lutzomyia, foram considerados vetores suspeitos ou comprovados. Devido ao seu caráter focal, a compreensão da dinâmica da LCA a nível local é imprescindível para a implementação de medidas de controle eficazes. Este trabalho consiste de uma revisão narrativa ...